A treatment within sight: challenges in the development of stem cell-derived photoreceptor therapies for retinal degenerative diseases - Beaver, Davinia; Limnios, Ioannis Jason (Frontiers in Transplantation, 2023)
Stem cell therapies can potentially treat various retinal degenerative diseases, including age-related macular degeneration (AMD) and inherited retinal diseases like retinitis pigmentosa. For these diseases, transplanted cells may include stem cellderived retinal pigmented epithelial (RPE) cells, photoreceptors, or a combination of both. Although stem cell-derived RPE cells have progressed to human clinical trials, therapies using photoreceptors and other retinal cell types are lagging. In this review, we discuss the potential use of human pluripotent stem cell (hPSC)-derived photoreceptors for the treatment of retinal degeneration and highlight the progress and challenges for their efficient production and clinical application in regenerative medicine.